Modular Microstructured Reactors for Pilot‐ and Production Scale Chemistry. Issue 1 (3rd December 2014) - Ghaini, Aras; Balon‐Burger, Monika; Bogdan, Anca; Krtschil, Ulrich; Löb, Patrick
Abstract In recent years, two strategies in continuous‐flow plant technology attracted strengthened interest: First, the use of microstructured devices as a new tool for process intensification and second, the modularity of interchangeable devices which leads to more flexibility. To take advantage of both, these approaches were combined within the EU‐project CoPIRIDE. Microstructured modular reactors were fabricated by novel manufacturing techniques. Different types of such reactors were characterized in terms of reaction engineering. Residence time distribution, heat transfer performance, pressure drop, and liquid‐liquid mixing performance were investigated.